Finding logic models for sustainable marine development that deliver on social equity - Ota, Yoshitaka; Singh, Gerald; Clark, Timothy; Schutter, Marleen; Swartz, Wilf; Cisneros-Montemayor, Andrés (2022)
Sustainable development is often represented as contributing to desirable outcomes across economic, environmental, and social goals, yet policies and interventions attempting to deliver sustainable development often disagree on the order in which these categories of goals should be addressed. In this Essay, we identify and review 5 approaches (called logic models) for sustainable development in ocean systems based on existing policies and interventions and consider the evidence for their contributions to equity—the ultimate goal of sustainable development according to the UN Sustainable Development Goals (SDGs). Two of the 5 logic models prioritize economic growth and lead to social and environmental benefits, 2 prioritize environmental health as a prerequisite for sustainable economic and social benefits, and the final logic model is community driven and prioritizes social dimensions. Looking towards the 2030 maturation of the SDGs, we will need to understand what models are best suited to deliver on equity gains and prevent future inequities in development and how best to operationalize them.